CHEMICAL AND MINERAL COMPOSITION OF TEN ECOMONICALLY IMPORTANT FISH SPECIES IN THE SATT AL- ARAB RIVER AND IRAQI MARINE WATER NORTHERN WEST ARABIAN GULF - & et al., Alhamadany (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This  study was  aimed to determine and compared the chemical composition and some of the main minerals of ten economically important fish species from the Shatt Al-Arab River; Leuciscus vorax. Cyprinus carpio. Hypophthalmichthys molitrix. Ctenopharyngodon idella and Mesopotamichthys sharpeyi. And Iraqi coastal water to the NorthernWast Arabian gulf; Acanthopagrus arabicus. Otoliths ruber. Mugil cephlus. Tenualosa ilisha and Pampus argenteus. Moisture ranged from 65.65±1.81 % to 77.94±0.799 %. Protein from 15.81±0.893 to 19.44±0.418 %. Fat from 0.974±0.049 to 6.461±0.489 %. Ash from 0.886±0.03 % to 2.127±0.279 percent  and caloric  value was ranged from 116.173±2.7645 to 215.26±11.3828 kcal/100g. Main minerals; calcium. Potassium. Phosphorus and Iron ranged from 15.98 to 93.49. 53.34 to 839.92. 249.36 to 686.61and  0.52 to 11.92 mg ∕100g of the fish muscle. Respectively. M. cephlus was the highest in contents of calcium and potassium. While C. carpio was highest in phosphorous and Iron. Mineral elements as the following sequence K > P > Ca > Fe. Muscle tissues. The results showed that fishes from Shatt Al-Arab and Iraqi marine waters provide a strong supply of protein. Lipid and metals. These results can be used as useful references for consumers in order to choose fish based on their quality and nutritional contents.